Assessment of human activities and its effects on forest management: a survey of charcoal producers in the Sekyere Central District of Ghana - Honger, J. O.; Lambon, J. B.; Anambam, D. Y. (IOP, 2023)
A survey to assess the effects and sustainability of charcoal production on the local vegetation cover was conducted in the Sekyere Central District of Ashanti region from December 2017 to April 2018. The study involved the use of structured questionnaires, focus group discussions(FGDs), key informants, secondary data and field observation by reconnaissance survey. The socio-economic survey was to identify who in the district is undertaking charcoal production as an economic venture, how widespread the activity is, and the preferred tree species being harvested to produce charcoal. In the field survey, the vegetation types in the study area were identified in a reconnaissance survey as secondary forests with increasing grassland. The relative abundance of tree species which could be used for charcoal production was also identified and quantified. A 640-meter square plot was delimited and divided into 64 square plots within each of which five-meter quadrats were marked at random and presence or absence was recorded for the individual tree species. The results of the study indicated that charcoal production is widely carried out throughout the district especially in the Afram Plains portion. It is practiced by the Akan and the Sissala ethnic groups who have very little education. Female producers(8%)were less than their male counterparts. Majority (73%) of the producers was 31 and above years whiles those of 30 years and below was 27%. The study revealed that most tree species are becoming rare and are only common in the protected area (Kogyae strict natures reserve) in the district.
Research Article
Keywords: charcoal production; reconnaisance survey; quadrats; relative abundance